As Irmandades Religiosas de Africanos e Afrodescendentes The Brazilian Afro-Descendants' Catholic Brotherhoods - de Carvalho Cruz, Teresa Cristina (PerCursos, 2008)
Neste artigo destaco as irmandades religiosas no que se refere ao catolicismo e as experiências africanas no século XIX no Brasil. As irmandades erigidas por “africanos e afrodescendentes” foram de fundamental importância para compreensão de uma sociedade que tinha em sua base a escravidão. A morte, momento tão ritualizado ficou sob cuidado dessas associações. Era por meio das irmandades que os afrodescendentes buscavam mostrar aos seus senhores que também faziam parte da sociedade, mesmo que no dia-a-dia isso não fosse percebido. Os senhores sentiam-se meio que impotentes já que não podiam impedir seus cativos de comparecer as festas, solenidades e enterros proporcionados por essas instituições. As irmandades negras representam na história cultural do Brasil uma expressão da prática religiosa/cultural das populações africanas, no qual subexistem certos costumes herdados pelo passado africano. Palavras-chave: Africanos e afrodescendentes. Rituais. Irmandades religiosa. Escravidão. História cultural do Brasil. Abstract: This article analyzes the Brazilian Afro-descendant catholic brotherhoods in Desterro in the 19th century. These catholic brotherhoods were formed specifically for Africans and their descendants and are fundamental in understanding social relationships in a society based on slavery. Through these catholic brotherhoods the Africans and their descendants thought to carve out a social space in a society that only recognized them as slaves. The slave owners could not impede their slaves to participate in the social events of the brotherhoods that included ritual ceremonies, such as the ritual ceremony of death. The Brazilian Afro-descendant catholic brotherhoods are important for the cultural history of Brazil, because they provided an opportunity for the African population and their descendants to express their religious/cultural practices, some of which were inherited from Africa. Keywords: Brazilian Afro-descendants. Rituals. Catholic brotherhoods. Slavery. Cultural history of Brazil.